2020
DOI: 10.1259/bjr.20190829
|View full text |Cite
|
Sign up to set email alerts
|

An update on effects of ionizing radiation exposure on the eye

Abstract: The International Commission on Radiological Protection (ICRP) has considered for over 60 years that the lens of the eye is among the most radiosensitive tissues, and has recommended dose limits for the lens to prevent occurrence of vision impairing cataracts (VICs). Epidemiological evidence that doses much lower than previously thought produce cataracts led ICRP to recommend reducing dose threshold for VICs and reducing an occupational equivalent dose limit for the lens in 2011, when only a single threshold o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 60 publications
1
36
0
2
Order By: Relevance
“…A PRV of the lens has already been established in dogs 6 . The lens is exclusively sensitive already to low doses of radiation and cataract formation can lead to loss of vision 2,35 . Cataract formation is, however, a non‐life‐threatening disease and can be treated with phacoemulsification surgery to restore vision 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A PRV of the lens has already been established in dogs 6 . The lens is exclusively sensitive already to low doses of radiation and cataract formation can lead to loss of vision 2,35 . Cataract formation is, however, a non‐life‐threatening disease and can be treated with phacoemulsification surgery to restore vision 36 .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of epidemiological evidence, it was assumed that the progression of opacities into vision-impairing cataracts had no dose rate effect. The above recommendations are based on epidemiological support since there are a small number of studies providing explicit biological, mechanistic evidence at doses <2 Gy [144,145].…”
Section: Promising New Preventive/mitigative Agents Currently Under Pmentioning
confidence: 99%
“…Retinal DNA damage may be caused by mitochondrial oxidative stress in experimental autoimmune uveitis (Nguyen and Rao 2010). Ocular diseases (i.e., diabetic retinopathy, retinal arteriolosclerosis, retinal degeneration and glaucoma), including fibrotic eye diseases, were reported in systemic inflammation-prone atomic bomb survivors exposed to a mean dose of $0.5 Gy of mainly low-LET IR (Minamoto et al 2004;Hamada et al 2019). However, even low doses of high-LET, high-charge, high-energy ionsa unique feature of galactic cosmic rays affect the retinal vasculature, causing apoptosis of retinal endothelial cells in mice (Mao et al 2018).…”
Section: Ocular Inflammation Including Uveitismentioning
confidence: 99%
“…Barnard et al (2019) recently found that murine LECs display an inverse dose-rate response, at doses 0.5-2.0 Gy, in terms of DNA damage signaling. Further investigation into the source of this observed response and the implications for the lens is required (Hamada et al 2019).…”
Section: Biological Mechanism: Lenticular Ion Transportmentioning
confidence: 99%
See 1 more Smart Citation